2021
DOI: 10.1097/inf.0000000000003042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID-19 Vaccine Refusal in Parents

Abstract: Objective: The frequency of vaccine refusal, which is associated with many factors, is increasing worldwide. The aim of this study was to predict the frequency of vaccine refusal against domestic and foreign COVID-19 vaccines and identify the factors underlying refusal. Methods: A survey consisting of 16 questions about COVID-19 vaccination was conducted either face-to-face or online with 428 parents who agreed to participate in the study. The parents had children who were inpatients or outpatients in the Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
193
7
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(233 citation statements)
references
References 12 publications
28
193
7
5
Order By: Relevance
“…Of notable importance, over 70% of the respondents in our survey reported a positive attitude to get COVID-19 vaccination for themselves, their spouses and children. This vaccination willingness was much higher than those among parents in England (55.8% for themselves and 48.2% for children) ( Bell et al, 2020 ), Turkey (33.9%-62.6% for themselves, 28.9%-56.8% for children) ( Yigit et al, 2021 ), Kuwait (44.2% for children) ( AlHajri et al, 2021 ), and multinational surveys (65.0%-69.2%for children) ( Goldman et al, 2020 ; Skjefte et al, 2021 ), but lower than that in Italy (over 90% for children) ( Pierantoni et al, 2021 ). Despite the difference of study sites, the willingness to vaccinate children in our survey were in line with a previous survey among factory workers in Shenzhen (72.6%) ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
“…Of notable importance, over 70% of the respondents in our survey reported a positive attitude to get COVID-19 vaccination for themselves, their spouses and children. This vaccination willingness was much higher than those among parents in England (55.8% for themselves and 48.2% for children) ( Bell et al, 2020 ), Turkey (33.9%-62.6% for themselves, 28.9%-56.8% for children) ( Yigit et al, 2021 ), Kuwait (44.2% for children) ( AlHajri et al, 2021 ), and multinational surveys (65.0%-69.2%for children) ( Goldman et al, 2020 ; Skjefte et al, 2021 ), but lower than that in Italy (over 90% for children) ( Pierantoni et al, 2021 ). Despite the difference of study sites, the willingness to vaccinate children in our survey were in line with a previous survey among factory workers in Shenzhen (72.6%) ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
“…Nevertheless, unlike drugs, problems arising from vaccine administration are frequently less accepted by the general population. Although benefits of vaccination clearly outweigh the risks, fear of adverse reactions (real or perceived) may deter many people from adherence to the vaccination campaign (Yigit, Ozkaya-Parlakay, and Senel 2021). The World Health Organization updated guidelines defined 5 types of adverse events following immunisation: (i) vaccine product-related reaction; (ii) vaccine quality defect-related reaction; (iii) immunisation error-related reaction; (iv) immunisation anxiety-related reaction; and (v) coincidental event (WHO 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of vaccine hesitancy literature during the pandemic has been devoted to hesitancy in adults about COVID-19 vaccination for adults. In our review, we found only two publications studying parental COVID-19 vaccine hesitancy for their children: Yigit et al reported that 56.8% would vaccinate their child with a domestic COVID-19 vaccine [8] and Rhodes et al noted parental unwillingness to vaccinate their child with the COVID-19 vaccine [9]. We found only one study on the influence of the pandemic on influenza vaccine hesitancy: Goldman et al showed that higher level of caregiver concern about having COVID-19 was associated with increased intent to vaccinate against influenza [10].…”
Section: Introductionmentioning
confidence: 94%